Hunting for Knowledge: Using a Scavenger Hunt to Orient Graduate Veterinary Students. - Caitlin Pike; Kristine M. Alpi (Issues in Science and Technology Librarianship)
Active participation in orientation is hoped to increase understanding and use of library resources and services beyond the effect of tours or welcome lectures. Timed scavenger hunts have been used to orient undergraduate and medical students to academic libraries. This report describes the planning, execution, and evaluation of an untimed iPod-documented scavenger hunt in 2012 for first-year graduate veterinary students, and the modification and execution of the hunt for new students in 2013. Findings about the hunt's utility as a learning opportunity, based on student participation, staff experiences, and student and staff perceptions, inform recommendations for the characteristics of a scavenger hunt that facilitates hands-on learning in the library while placing reasonable demands on library staff. [ABSTRACT FROM AUTHOR]